Application of Inquiry Learning-Based LKPD to Improve Students' Interpersonal Intelligence (International Journal of Active Learning, 2023)
This study aims to improve interpersonal intelligence in the process of learning discussions, practicums, and presentations in schools. This research method is descriptive qualitative through in-depth interviews, direct observation and study of documents regarding the process of observing student collaboration (interpersonal). The focus of this research is the activeness of students during discussions, students' skills during practicum to develop Inquiry Learning-based worksheets and interpersonal intelligence. The data obtained is then analyzed, verified and constructed into a scientific knowledge that can be utilized as a source of learning in schools. The results and conclusions of interpersonal intelligence increase with a good average using inquiry learning-based worksheets.